Key drivers of student satisfaction in public higher education institutions in Pahang, Malaysia - Noraine Bahari; Siti Nur Aliah Zahir; Suhaidah Hussain; Mohamad Hafiz Rosli; Muhammad Ashraf Fauzi; Arifha Mohamad; Najaa Abd Mubin (Institute of Advanced Engineering and Science, 2026)
In today’s educational landscape, understanding key student satisfaction is essential for institutions striving to enhance educational quality and foster positive student experiences. The sustainability of public higher education institutions (PHEIs) depends heavily on students’ enrolments. In an effort to attract and retain students, factors contributing to student satisfaction should be taken into consideration from each educational institutions to make the academic program are kept relevant throughout the time. This study aims to examine the factors influencing student satisfaction in PHEIs in Pahang, Malaysia. A quantitative survey was conducted among 120 students from various public universities in Pahang, Malaysia. Descriptive statistics, correlation, and multiple regression analysis were conducted using SPSS 26 to assess their perceptions of three key factors: quality of teaching and learning (QT), quality of facilities and infrastructure (QF), and quality of career and future opportunities (QC). The findings reveal that QT has a significant negative effect on student satisfaction (β=–0.468, p<0.001), while QC show a significant positive effect (β=0.327, p=0.015). In contrast, QF has no significant influence (β=0.125, p=0.301). Therefore, this study provides insights for educational policy makers to enhance student satisfaction strategy in PHEIs especially in focusing on career opportunities of students.